Winding type lithium ion battery

By setting a through-hole structure in the arc area of ​​the negative electrode sheet of the winding type lithium ion battery and adding boron-containing compounds, the problem of arc lithium-ion battery arc excision of the battery under fast charging is solved, which extends the cycle life and improves the kinetic performance.

CN119725786APending Publication Date: 2025-03-28ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510071064.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The wound type lithium-ion battery is prone to arc lithium-ion arcing under fast charging conditions, resulting in deterioration in performance.

Method used

By setting a through-hole structure in the arc area of ​​the negative electrode sheet and adding a boron-containing compound to the electrolyte, the ratio of the pore size D of the through-hole structure and the content A1 of the boron-containing compound is controlled to ensure 20≤D/A1≤120.

Benefits of technology

It improves the cycle life of lithium-ion batteries under fast charging conditions, reduces the situation of arc lithium-ion separation, and improves the dynamic performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245713860000051
    Figure BDA0005245713860000051
  • Figure BDA0005245713860000121
    Figure BDA0005245713860000121
  • Figure BDA0005245713860000131
    Figure BDA0005245713860000131
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a winding type lithium ion battery which comprises an electrolyte, a negative plate and a positive plate, the electrolyte comprises an organic solvent and a first additive; the first additive comprises a boron-containing compound, and the mass ratio of the boron-containing compound in the electrolyte is A1%; the arc area of the negative plate is provided with a through hole structure, and the aperture of the through hole structure is D [mu] m; 20 < = D / A1 < = 120. The through hole structure is arranged in the arc area of the negative plate, and the aperture D of the through hole is matched with the content A1 of the boron-containing compound in the electrolyte, so that arc lithium precipitation of the winding type lithium ion battery under fast charge is improved, and the cycle life of the lithium ion battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a wound lithium-ion battery. Background Art

[0002] Lithium-ion batteries are usually produced by winding or laminating. Lithium-ion batteries with a wound structure are widely used in various soft-pack and cylindrical batteries because of their high production efficiency and low cost. Compared with laminated batteries, wound lithium-ion batteries have a special arc area. In this area, since the positive and negative electrodes are not strictly parallel and there is a certain gap between the electrodes, lithium deposition is more likely to occur at the arc under fast charging conditions, causing the performance of lithium-ion batteries to deteriorate.

[0003] Based on the increasingly higher requirements for the energy density and fast charging performance of lithium-ion batteries, wound lithium-ion batteries urgently need to solve the problem of arc lithium deposition under fast charging. Summary of the invention

[0004] The present invention provides a wound lithium-ion battery, aiming to solve the problem of arc lithium deposition in the wound lithium-ion battery during fast charging.

[0005] The present invention provides a wound lithium-ion battery, comprising an electrolyte, a negative electrode sheet, and a positive electrode sheet; the electrolyte comprises an organic solvent and a first additive; the first additive comprises a boron-containing compound, and the mass proportion of the boron-containing compound in the electrolyte is A1%; the negative electrode sheet comprises a plurality of straight regions and a plurality of arc regions; the arc region is provided with a through-hole structure, and the aperture of the through-hole structure is Dμm; wherein A1 and D satisfy: 20≤D / A1≤120. The present invention improves arc lithium precipitation of the wound lithium-ion battery and prolongs the cycle life of the lithium-ion battery by cooperating the aperture D of the through-hole structure provided in the arc region of the negative electrode sheet with the boron-containing compound content A1 in the electrolyte.

[0006] Additional aspects and detailed advantages of embodiments of the present invention will be described and shown in part in the following description, or will be explained through the implementation of embodiments of the present invention. DETAILED DESCRIPTION

[0007] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0008] In the description of the present invention, it should be noted that the terms “first” and “second” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0009] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0010] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0011] The present invention provides a wound lithium-ion battery, comprising an electrolyte, a negative electrode sheet, and a positive electrode sheet; the electrolyte comprises an organic solvent and a first additive; the first additive comprises a boron-containing compound, and the mass proportion of the boron-containing compound in the electrolyte is A1%; the negative electrode sheet comprises a plurality of first straight areas and a plurality of first arc areas, and the positive electrode sheet comprises a plurality of second arc areas corresponding to the first arc areas; the first arc area is provided with a through hole structure, and the aperture of the through hole structure is Dμm; 20≤D / A1≤120.

[0012] When the above conditions are met, the cycle life of the battery under fast charging conditions can be improved. The inventor speculates that the implementation mechanism is:

[0013] Under fast charging conditions, the pores of these through-hole structures can provide more channels for lithium ions to embed into the negative electrode, reducing the polarization of lithium ions in this area, thereby improving the fast charging capability of the lithium-ion battery; at the position of the arc region, the two faces of the negative electrode sheet are asymmetric, the negative electrode material on one side is subjected to compressive stress, and the material on the other side is subjected to tensile stress. Therefore, when lithium ions are embedded into the negative electrode material, the negative electrode resistance on the side subjected to compressive stress is greater, and lithium precipitation is more likely to occur, affecting the cycle performance; the present invention sets a through-hole structure at the position of the arc region, and since the electrolyte and lithium ions can shuttle between the two sides of the negative electrode sheet through the through-hole structure, under fast charging conditions, the excess lithium ions on the side subjected to compressive stress can migrate to the other side through these holes, avoiding the occurrence of lithium precipitation in advance, thereby improving the cycle performance;

[0014] In addition, the present invention adds boron-containing compounds to the electrolyte, which can make the SEI film denser, further improve the stability of the SEI film and the ability to conduct lithium ions, and improve the cycle performance. Specifically, when the SEI film formed on the surface of the negative electrode is too loose, it will more easily adsorb various components in the electrolyte and occupy the area near the pore wall. In addition, the volume expansion of the negative electrode material during the lithium insertion process can easily lead to the narrowing of the space in the pore of the through-hole structure that can actually be used for the solvated lithium ions to shuttle, thereby affecting the improvement effect of the through-hole structure on arc lithium precipitation. The boron-containing compound can preferentially form a relatively stable SEI film on the surface of the electrode, which can inhibit the excessive decomposition of the solvent in the electrolyte and avoid the accumulation of decomposition products around the pore, thereby maintaining the smooth flow of the pore, and then ensuring the rapid shuttle of the solvated lithium ions. Therefore, the present invention improves the surface state of the pore ends and pore walls of the through-hole structure through the use of boron-containing compounds, making the SEI film denser and improving the cycle performance.

[0015] At the same time, by controlling A1 and D to satisfy: 20≤D / A1≤120, that is, by comprehensively regulating the ratio of the perforation size to the content of the boron-containing compound in the through-hole structure, it can effectively ensure that there is actually enough space in the pores for the solvated lithium ions to shuttle, delay the occurrence of lithium precipitation, and thus improve the cycle stability of lithium-ion batteries under fast charging. As an example, D / A1 can be 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120 or within the range of any two of the above values. Specifically, when the diameter of the perforation is relatively large and the content of the boron-containing compound is relatively low, that is, when D / A1 is greater than 120, the solvent and other components are used to form the film in the later stage, which will cause the thickness of the SEI film to grow faster in the later stage, reduce the desorption efficiency of the solvated lithium ions, and thus lead to limited improvement in the arc lithium deposition of the lithium ion battery, affecting the cycle performance; and when the diameter of the hole is relatively small and the addition amount of the boron-containing compound is relatively high, that is, when D / A1 is less than 20, the initially formed SEI film is relatively thick and the pores of the through-hole structure are relatively small, the solvated lithium ion shuttling resistance is relatively large, and the improvement of the arc lithium deposition is also relatively limited, affecting the cycle performance; therefore, the present invention optimizes the rapid shuttling performance of lithium ions and reduces the lithium deposition through comprehensive control of D / A1, thereby improving the cycle performance.

[0016] In an optional embodiment, the arc region of the negative electrode sheet has a through-hole structure with an aperture Dμm satisfying 20≤D≤200, preferably 50≤D≤150. As an example, the value of D can be 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 or within the range formed by any two of the above values. The through-hole structure runs through the entire negative electrode sheet. When the size of the through-hole structure is too small, the area of ​​kinetic improvement is relatively narrow, and the improvement of lithium precipitation is not obvious; when the size of the through-hole structure is too large, the weight loss rate of the negative electrode sheet caused by drilling is too high, the lithium storage sites at the negative electrode arc become fewer, and the local lithium flux heterogeneity is aggravated, which will lead to the early occurrence of lithium precipitation; the present invention can ensure the rapid shuttling performance of lithium ions by controlling the aperture D of the through-hole structure.

[0017] It can be understood that, due to the limitation of processing accuracy, the above-mentioned through-hole structure is not limited to a circular hole, but can also be an elliptical, rectangular, triangular or other irregularly shaped hole. The aperture D can be measured under the SEM field of view of the negative electrode surface, and the distance between the two farthest points in a single hole shape is regarded as the aperture.

[0018] In an optional embodiment, the mass proportion of the boron-containing compound in the electrolyte in the present invention is A1%, and by controlling 0.3≤A1≤2, the occurrence of lithium precipitation can be delayed, thereby improving the cycle stability of the lithium-ion battery under fast charging. As an example, the mass proportion of the boron-containing compound in the electrolyte A1% can be 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2% or within the range composed of any two of the above values. Specifically, if the amount of boron-containing compound added is too little, the effect on the properties of the SEI film is small, and the improvement of the cycle performance of the lithium-ion battery is limited; if the amount of boron-containing compound added is too much, due to its strong film-forming property, it is easy to cause the initial SEI film to be too thick, which is not conducive to the lithium-ion battery to obtain better fast charging performance; the present invention improves the cycle stability of the lithium-ion battery under fast charging by controlling the mass proportion of the boron-containing compound.

[0019] In an optional embodiment, the boron-containing compound is selected from one or more of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium dicyanooxalatoborate, lithium bismalonate borate, lithium (2-fluoromalonate) difluoroborate, lithium bis(salicylate)borate, lithium methanedisulfonate difluoroborate, lithium bis(difluorophosphoryloxy)difluoroborate, and lithium bis(1,1,1,4,4,4-hexafluorobutyl-2,3-diol)borate.

[0020] In an optional embodiment, the SEI film formed by the boron-containing compound is more likely to produce gas at high temperature. Therefore, the present invention further adds a sulfur-containing heterocyclic compound to the electrolyte. The sulfur-containing heterocyclic compound can also form a film at the positive and negative electrodes. After the film is formed, the SEI film can contain a certain amount of sulfate or sulfonate structure. These sulfur-containing structures can form a connection with the borate structure formed by the lithium ions or other metal ions in the SEI film and the boron-containing compound, thereby achieving the purpose of inhibiting high-temperature gas production of lithium-ion batteries.

[0021] In an optional embodiment, the mass proportion of the sulfur-containing heterocyclic compound in the electrolyte is A2%, 1≤A2≤4, and 1.5≤A2 / A1≤5 is further controlled to effectively ensure that gas production is suppressed while achieving better kinetics and cycle performance of the lithium-ion battery. As an example, the mass proportion A2% of the sulfur-containing heterocyclic compound in the electrolyte can be 1%, 1.3%, 1.5%, 1.8%, 2%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4% or within the range of any two of the above values; A2 / A1 can be 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or within the range of any two of the above values. Specifically, if the amount of sulfur-containing heterocyclic compounds added is too small, the effect of inhibiting high-temperature gas production cannot be achieved; if the amount added is too high, the dynamics of lithium-ion batteries will be degraded, resulting in the occurrence of lithium precipitation; at the same time, when the content of boron-containing compounds is high and the content of sulfur-containing heterocyclic compounds is low, the SEI film components formed by sulfur-containing heterocyclic compounds can only be connected with SEI film components formed by a small amount of boron-containing compounds, and it is difficult to achieve a good effect of inhibiting gas production; when the content of boron-containing compounds is low and the content of sulfur-containing heterocyclic compounds is high, the dynamic degradation performance of the sulfur-containing heterocyclic compounds on the SEI film is dominant, resulting in a decrease in the dynamics and cycle performance of lithium-ion batteries. Therefore, the present invention achieves better dynamics and cycle performance of lithium-ion batteries while ensuring the inhibition of gas production through the mass proportion of sulfur-containing heterocyclic compounds in the electrolyte A2, and the range value of A2 / A1.

[0022] In an optional embodiment, the sulfur-containing heterocyclic compound comprises at least one of the following structural formulas:

[0023]

[0024] In an optional embodiment, the organic solvent in the electrolyte includes a first solvent and a second solvent; the first solvent is selected from carboxylic acid ester compounds containing 4-6 carbon atoms; and the second solvent is a solvent molecule with film-forming properties.

[0025] The first solvent of the specific type in the present invention has good stability and kinetic performance, can broaden the lithium precipitation window of the lithium ion battery, and improve the kinetic performance of the lithium ion battery. The second solvent of the specific type in the present invention has good film-forming properties, can form a film on the positive and negative electrodes, maintain the stability of the positive and negative electrode materials, and extend the cycle life of the lithium ion battery.

[0026] In an optional embodiment, the first solvent is selected from one or more of ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, methyl isobutyrate, ethyl isobutyrate and various fluorinated compounds of these compounds; the second solvent is selected from ethylene carbonate and / or fluoroethylene carbonate.

[0027] In an optional embodiment, the amount of the first solvent added to the electrolyte is S1 wt%, 30≤S1≤70; the amount of the second solvent added to the electrolyte is S2 wt%, 15≤S2≤40; preferably, controlling 1.5≤S1 / S2≤3 can effectively and timely repair the SEI film and reduce lithium plating, thereby achieving better cycle performance. As an example, the amount S1 wt % of the first solvent added in the electrolyte can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or within the range formed by any two of the above values; the amount S2 wt % of the second solvent added in the electrolyte can be 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40% or within the range formed by any two of the above values; S1 / S2 can be 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, 3.0 or within the range formed by any two of the above values. Specifically, when the amount of the first solvent added is too high and the amount of the second solvent added is too small, although the kinetics of the lithium-ion electrolyte is good, due to the low content of the second solvent, the damaged solid electrolyte membrane (SEI membrane) cannot be repaired in time in the later stage of the cycle, which leads to a reduction in the cycle life of the lithium-ion battery; when the amount of the first solvent added is too small and the amount of the second solvent added is high, the kinetics of the lithium-ion electrolyte at this time is poor, which easily leads to the occurrence of lithium precipitation in the early stage of the cycle. Therefore, the present invention achieves better cycle performance by comprehensively controlling S1 / S2.

[0028] In an optional embodiment, in the first arc region, the spacing between adjacent through-hole structures is 100-800μm, preferably 200-600μm, which effectively ensures the activity of the negative electrode material and reduces lithium precipitation, thereby ensuring the cycle performance. As an example, the spacing between adjacent through-hole structures can be 100μm, 150μm, 200μm, 250μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm or within the range of any two of the above values. Specifically, if the spacing between the through-hole structures is too small, the negative electrode powder attached between the through-hole structures is easy to loosen, causing the negative electrode material to detach from the current collector and deactivate, and the battery cycle performance decreases; when the spacing between the holes is too large, the area where the holes are not set is more prone to lithium precipitation due to differences in dynamics and through-holes, which will also affect the cycle performance of the battery. Therefore, the effect of improving the cycle performance is effectively achieved by controlling the spacing between adjacent through-hole structures.

[0029] In an optional embodiment, the distribution width of the through-hole structure in the first arc region is 2-10mm, which reduces arc lithium precipitation while avoiding belt breakage and improves the cycle performance. As an example, the distribution width of the through-hole structure in the arc region can be 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm or in the range composed of any two of the above values. When the distribution width of the through-hole structure in the arc region is small, although it can improve the fast charging performance of the lithium-ion battery to a certain extent and delay the time of arc lithium precipitation, the dynamics of the arc region where the through-hole structure is not distributed is still relatively poor, and it will become a site for easy lithium precipitation; when the distribution width of the through-hole structure in the arc region is large, it will not only lead to a decrease in energy density, but also increase the area where the negative electrode sheet is mechanically weak, resulting in more likely to break the belt during winding; therefore, the present invention achieves the effect of avoiding belt breakage and reducing the occurrence of lithium precipitation by controlling the distribution width of the through-hole structure in the arc region within the above range, and effectively improves the cycle performance.

[0030] In an optional embodiment, the porosity of the negative electrode sheet is controlled to be 10%-40%, which effectively improves the cycle life of the battery under better fast charging performance. As an example, the porosity can preferably be 10%, 15%, 20%, 25%, 30%, 35%, 40% or within the range formed by any two of the above values. Specifically, if the porosity is too small, the wettability and liquid retention of the electrolyte are poor, which is not conducive to the fast charging and cycle life improvement of the lithium-ion battery; if the porosity is too large, not only the energy density of the battery is reduced, but also the electrical contact between the powder particles is poor, which is not conducive to the fast charging performance of the lithium-ion battery; by controlling the porosity of the negative electrode sheet, it is effectively achieved to improve the cycle life of the battery under better fast charging performance.

[0031] In an optional embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, and the silicon content in the negative electrode active material layer is controlled to be 2%-30%, which can ensure the cycle life of the battery under the premise of achieving a higher energy density. As an example, the silicon content in the negative electrode active material layer can be 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30% or in the range of any two of the above values. Specifically, if the silicon content is too low, not only the energy density is limited, but also the local stress-strain effect is more obvious due to the relatively dispersed distribution of silicon particles, which is easy to cause interface problems in local areas; if the silicon content is too high, the negative electrode powder is easy to loosen due to the large volume change of silicon, especially the negative electrode powder at the arc, which is itself in a compressed or stretched state, and the stress-strain effect of the silicon particles is more likely to deteriorate the adhesion of the powder at this location, thereby aggravating the arc lithium precipitation and affecting the cycle life of the battery; the present invention effectively improves the cycle performance of the battery while ensuring a higher energy density by controlling the silicon content in the negative electrode active material layer within the above range.

[0032] In an optional embodiment, the wound lithium-ion battery requires that the powder on the pole piece can be firmly attached to the current collector during the winding process without cracking or falling off; the present invention controls the distribution particle size Dv10: 3-8μm, Dv50: 8-15μm, Dv90: 15-25μm of the powder in the negative electrode active material layer. Through the above-mentioned distribution particle size control of the powder, after uniform mixing and coating, the particles with smaller particle sizes can be distributed between the gaps of larger particles, which is not only conducive to improving the compaction density of the negative electrode powder, but also improves the flexibility of the negative electrode sheet. At the same time, the particle size ratio of the negative electrode powder particles not only affects the compaction density and porosity of the negative electrode sheet powder, but also has a greater impact on the flexibility and bending resistance of the pole sheet.

[0033] As an example, the Dv10 of the powder in the negative electrode active material layer can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or within the range formed by any two of the above values; the Dv50 of the powder in the negative electrode active material layer can be 8μm, 10μm, 13μm, 15μm or within the range formed by any two of the above values; the Dv90 of the powder in the negative electrode active material layer can be 15μm, 18μm, 20μm, 23μm, 25μm or within the range formed by any two of the above values.

[0034] In an optional embodiment, in order to ensure that the positive electrode capacity is higher than that of the negative electrode, the positive electrode sheet can be subjected to a pore-making treatment; that is, the second arc region is provided with a concave hole structure so that the ratio of the negative electrode capacity to the positive electrode capacity reaches 1.05-1.10, and the deposition of lithium metal on the negative electrode surface is prevented by controlling the positive-negative electrode capacity ratio, thereby improving the cycle life. Specifically, the location of the positive electrode sheet is the second arc region of the positive electrode sheet. The present invention controls the diameter of the concave hole at the positive electrode arc to be 5-50μm, and the spacing between the holes is 50-300μm. After the concave hole is made at the positive electrode arc, the lithium storage margin of the corresponding negative electrode arc is relatively increased, which can further reduce the risk of arc lithium precipitation.

[0035] As an example, the diameter of the positive electrode concave hole can be 5 μm, 15 μm, 25 μm, 35 μm, 45 μm, 50 μm, or within the range formed by any two of the above values. The spacing between the holes can be 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, or within the range formed by any two of the above values.

[0036] In an optional embodiment, the positive electrode sheet can also achieve the same effect as the above-mentioned pore making by thinning, and the thinned area is the positive arc, that is, the thickness of the positive electrode active material layer in the second arc area is less than the thickness of the positive electrode active material layer in the adjacent positive electrode sheet area, and the present invention controls the thinned thickness to be 2-10μm. As an example, the thinned thickness of the positive electrode sheet can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, or within the range of any two of the above values.

[0037] It is understandable that the way to ensure that the positive electrode capacity is higher than that of the negative electrode is not limited to drilling or thinning. Reducing the surface density of the positive electrode coating and adjusting the gram capacity of the positive electrode by adjusting the formula are also feasible ways.

[0038] Negative electrode powder particle size test method: Particle sizes Dv10, Dv50, and Dv90 can be measured using a laser particle size test method. For example, a Malvern particle size tester is used for measurement. The test steps are as follows: The negative electrode material is dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03wt%) to form a mixture, and the mixture is ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing.

[0039] Negative electrode sheet porosity test method: gas replacement method is used for testing, and the specific method is as follows: after discharging the lithium-ion secondary battery to 0% SOC, disassemble and take out the negative electrode sheet, soak it in dimethyl carbonate (DMC) solvent for 12 hours, and then rinse it with DMC to remove the lithium salt attached to the electrode sheet. After drying, use a slicer to cut the negative electrode sheet into discs with a diameter of 12 mm, use a micrometer to measure the thickness of 20 discs, calculate the volume of each disc separately and sum them to obtain the sum of the volumes of the 20 discs V1; then use a true density meter (such as JW-M100A fully automatic true density tester) to test the true volume V2 of the 20 discs, where the test gas is helium and the test environment temperature is 25±2°C; the porosity of the negative electrode sheet is (V1-V2) / V1*100%.

[0040] Test method for silicon content in negative electrode active material layer: The silicon content in negative electrode material can be detected by X-ray energy dispersive spectrometer (EDS) or X-ray wavelength dispersive spectrometer configured by scanning electron microscope or transmission electron microscope, or by X-ray photoelectron spectroscopy, inductively coupled plasma, element analyzer and other instruments. For example, the disassembled negative electrode sheet can be obtained by slicer or argon ion milling instrument to obtain the cross section of the negative electrode sheet, and then surface scanning and quantitative analysis can be performed by EDS at an electron beam acceleration voltage of 15kV to obtain the silicon content; or, the negative electrode powder can be lightly scraped off from the negative electrode sheet, with a mass greater than or equal to 0.5g, and then the silicon content can be tested by inductively coupled plasma spectrometer after nitration with concentrated nitric acid; or, the powder of the negative electrode sheet can be scanned by X-ray photoelectron spectroscopy, and the silicon content can be obtained by peak identification and integration of the element peaks in the photoelectron spectrum using software such as Avantage and CasaXPS.

[0041] The negative electrode sheet of the battery in the present invention comprises a negative electrode current collector and a negative electrode active material layer on one or both sides of the surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, a binder, and a conductive agent, and the mass percentage of each component in the negative electrode active material layer is: 90-99.2wt% of the negative electrode active material, 0.3-5wt% of the conductive agent, and 0.5-5wt% of the binder.

[0042] The positive electrode sheet of the present invention comprises a positive electrode current collector and a positive electrode active material layer coated on one or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder. In the battery of the present invention, the mass percentage of each component in the positive electrode active material layer is: 90-99.2wt% of the positive electrode active material, 0.4-5wt% of the conductive agent, and 0.4-5wt% of the binder.

[0043] The present invention does not particularly limit the conductive agent in the positive electrode sheet and the negative electrode sheet, which can be selected from the conductive agents conventionally used in the art, including but not limited to at least one selected from conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.

[0044] The present invention does not particularly limit the binder in the positive electrode sheet and the negative electrode sheet, which can be selected from the binders conventionally used in the art, including but not limited to one or more of styrene-butadiene rubber emulsion, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, and carboxylated chitosan.

[0045] The positive electrode active material of the present invention is selected from one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, and lithium-rich lithium manganese oxide; the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.

[0046] According to the battery of the present invention, the electrolyte may further include other solvents, lithium salts and other additives.

[0047] The other solvents may be selected from propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), fluorobenzene, difluorobenzene, ethyl methyl carbonate, etc. The other solvents account for 0wt%-20wt% of the total mass of the electrolyte.

[0048] The lithium salt can be selected from lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethyl sulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxaloyl)phosphate. The lithium salt accounts for 12wt%-25wt% of the total mass of the electrolyte.

[0049] The other additives may be selected from one or more commonly used additives to further improve the cycle performance or high and low temperature performance of the battery, such as vinylene carbonate (VC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), propene sultone (PST), methylene disulfonate (MMDS), 1,3-propane sultone (PS), vinyl sulfate (DTD), tetravinylsilane (TVS), tris (trimethylsilyl) borate (TMSB), hexamethyldisilazane (HMDS), triphenyl phosphite (TPPi), pentafluoroethoxy cyclotriphosphazene (PFPN), succinonitrile (SN), adiponitrile (AND), glutaronitrile (GN), hexane trinitrile (HTCN), ethylene glycol bis (propionitrile) ether (DENE), glycerol trinitrile (TCP), 2,4,6-tricyano-1,3,5-triazine, etc. The total amount of the other additives added in the electrolyte accounts for 1wt%-8wt%.

[0050] The present invention does not specifically limit the preparation method of the lithium-ion battery, and the lithium-ion battery can be prepared by conventional preparation methods in the art. For example, the negative electrode sheet, the separator, and the positive electrode sheet are stacked in a certain manner so that the separator completely separates the positive and negative electrodes, and the negative electrode paste completely covers the positive electrode paste, and then a winding core is made by winding. Subsequently, an aluminum-plastic film is used for packaging and an electrolyte is injected. After vacuum packaging, aging, formation, shaping, sorting and other processes, a soft-pack lithium-ion battery is obtained.

[0051] The present invention is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the invention. In all examples and comparative examples of the present invention, the unit wt% represents mass percentage.

[0052] Example 1

[0053] A wound lithium-ion battery, the preparation process of which is as follows:

[0054] (1) Preparation of negative electrode sheet

[0055] The negative electrode active material (composed of 88wt% artificial graphite + 12wt% silicon carbon), styrene butadiene rubber (SBR), lithium polyacrylate, conductive carbon black (SP) and carbon nanotubes (CNTs) are mixed evenly in a mass ratio of 96.5:1.5:0.5:1.0:0.5, and then an appropriate amount of deionized water is added step by step to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on both surfaces of the copper foil by a coater; the coated copper foil is dried, and then the desired negative electrode sheet is obtained by rolling, slitting, arc punching and other processes. The position of the arc punching and the size of the hole are precisely located by the instrument. In this embodiment, the diameter of the through-hole structure at the arc of the negative electrode sheet is 80μm, the spacing between the holes is 300μm, the hole penetrates the entire negative electrode sheet, and the through-hole structure distribution width in the arc area is 5mm. In the negative electrode sheet, the porosity of the negative electrode sheet is 25%, the silicon content of the negative electrode active material layer is about 8%, and the distribution particle size of the powder in the negative electrode active material layer is Dv10: 5μm, Dv50: 10μm, and Dv90: 20μm.

[0056] (2) Preparation of positive electrode

[0057] Commercial lithium cobalt oxide (LiCoO2) material, polyvinylidene fluoride (PVDF), SP and carbon nanotubes (CNTs) are dry mixed in a mass ratio of 96.0:2.0:1.5:0.5. Subsequently, under the action of a vacuum mixer, an appropriate amount of N-methylpyrrolidone (NMP) is gradually added to mix into a uniform slurry. Subsequently, a coating machine is used to evenly coat the positive electrode active slurry on both surfaces of the aluminum foil; the coated aluminum foil is dried, and then the desired positive electrode sheet is obtained by roller pressing, slitting, arc pore making and other processes. In this embodiment, the diameter of the hole made at the arc of the positive electrode sheet is 25μm, the spacing between the holes is 150μm, the depth of the hole is 35μm, the width of the hole distribution area is 7mm, and the depth of the hole is less than the thickness of the single-sided paste, so that the positive and negative electrode capacity ratio (the ratio of negative electrode capacity / positive electrode capacity) reaches 1.08.

[0058] (3) Preparation of electrolyte

[0059] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC), fluoroethylene carbonate (FEC), n-propyl propionate (PP), and ethyl propionate (EP) are mixed uniformly in a mass ratio of 15:15:40:30. Then, 15wt% of LiPF6 based on the total mass of the electrolyte is quickly added thereto, and after dissolution, 2.0wt% of HTCN, 1.0wt% of lithium difluorooxalate borate (LiODFB), and 2.0wt% of the sulfur-containing substance of formula I are added based on the total mass of the electrolyte. After stirring evenly, the desired electrolyte is obtained after passing the tests of moisture, free acid, color, etc. In this embodiment, the addition amount of the first solvent (PP+EP) is 56wt% of the total mass of the electrolyte, the addition amount of the second solvent (EC+FEC) in the electrolyte is 24wt%, the addition amount of the first additive is 1wt%, and the addition amount of the second additive is 2wt%.

[0060] (4) Preparation of batteries

[0061] The negative electrode sheet prepared in the above steps, the commercial separator, and the positive electrode sheet prepared in the above steps are stacked in a certain way, so that the separator completely separates the positive and negative electrodes, and the negative electrode paste completely covers the positive electrode paste, and then a coil core with a certain thickness and width is made by winding. Subsequently, an aluminum-plastic film is used for packaging and the electrolyte prepared in the above steps is injected. After vacuum packaging, aging, formation, shaping, sorting and other processes, a soft-pack lithium-ion battery with a certain specification and energy density controlled at the same level is obtained. The energy density of the battery in this embodiment is controlled to be 800Wh / L.

[0062] The battery of the present invention has a lithium ion voltage test window of 3.0-4.53V.

[0063] Example 2

[0064] The difference between this embodiment and embodiment 1 is that when preparing the positive electrode sheet in step (2), no pore making treatment is performed, but a thinning treatment is performed at the arc, so that the positive-negative electrode capacity ratio (the ratio of negative electrode capacity / positive electrode capacity) at the arc after treatment reaches 1.08, and the other conditions are exactly the same as in embodiment 1.

[0065] Examples 3-14 and Comparative Examples 1-6

[0066] The difference between this embodiment and embodiment 1 is that the proportions of the substances in the electrolyte are different, and at the same time, the diameter D of the through-hole structure in the negative electrode sheet is different, and the specific settings are shown in Table 1 below.

[0067] Table 1

[0068]

[0069]

[0070] At the same time, the hole diameter of the positive electrode sheet is controlled so that the positive-negative electrode capacity ratio (the ratio of negative electrode capacity / positive electrode capacity) reaches 1.08. The other parameter conditions in this embodiment are the same as those in Example 1.

[0071] Comparative Example 7

[0072] The difference between this embodiment and embodiment 1 is that when the arc of the negative electrode sheet is punched, the punching depth is 35 μm, the same as that of the positive electrode sheet, that is, in this comparative example, the hole punched in the arc area of ​​the negative electrode sheet is a non-through hole structure.

[0073] Comparative Example 8

[0074] The difference between this embodiment and embodiment 1 is that no hole punching is performed on the negative electrode sheet.

[0075] Examples 15-25

[0076] The difference between this embodiment and embodiment 1 is that the types of substances in the electrolyte are different, and the specific settings are shown in Table 2 below.

[0077] Table 2

[0078]

[0079] The other conditions of this embodiment are the same as those of embodiment 1.

[0080] Embodiment 26-45

[0081] The difference between this embodiment and embodiment 1 is that the silicon content in the negative electrode sheet and the arrangement parameters of the through-hole structure are different, and the specific settings are shown in Table 3 below.

[0082] Table 3

[0083]

[0084]

[0085] At the same time, the hole diameter of the positive electrode sheet is controlled so that the positive-negative electrode capacity ratio (the ratio of negative electrode capacity / positive electrode capacity) reaches 1.08. The other parameter conditions in this embodiment are the same as those in Example 1.

[0086] Embodiment 46

[0087] The difference between this embodiment and embodiment 1 is that, when preparing the positive electrode sheet in step (2), no punching process is performed and no arc thinning process is used.

[0088] Experimental example

[0089] The lithium-ion batteries obtained in the examples and comparative examples were subjected to cycle performance tests and charging window confirmations, respectively.

[0090] 1. Cycle performance test:

[0091] In a constant temperature box at 25°C, the battery is charged to the upper limit voltage at an initial rate of 3C, and then charged at a constant voltage until the current drops to 0.05C. This is a charging process. After the charging process is completed, it is left to stand for 10 minutes, and then discharged to 3.0V at a rate of 0.7C. One charge and discharge process is a cycle.

[0092] 2. Confirmation of arc lithium deposition:

[0093] After the battery has been cycled for 400T, it is fully charged and disassembled to observe the lithium deposition at the arc. Grade A indicates no lithium deposition: the arc of the disassembly interface is all golden yellow, without any gray or silver lithium deposition spots. Grade B indicates slight lithium deposition: there are very thin gray-black spots or a small amount of silver-white lithium deposition spots on the surface of the golden negative electrode material at the arc. Grade C indicates more serious lithium deposition: most of the arc has gray-black or silver lithium deposition materials and the lithium deposition process is strip-shaped. Grade D indicates severe lithium deposition: not only is there obvious lithium deposition at the arc, but also lithium deposition occurs around the arc, showing a state of lithium deposition spreading from the arc to the surrounding area.

[0094] 3. Charging window confirmation:

[0095] In a constant temperature box at 25℃, charge at a constant current rate of 3C to the upper limit voltage and then charge at a constant voltage until the current drops to 0.05C, then discharge at a rate of 1C to 3.0V, and cycle for 20T. After fully charged, disassemble and observe the lithium deposition on the surface of the negative electrode sheet, among which Grade A means no lithium deposition: the arc of the disassembled interface is all golden yellow, without any gray or silver lithium deposition spots, Grade B means slight lithium deposition: there are very thin gray-black spots or a small amount of silver-white lithium deposition spots on the surface of the golden negative electrode material at the arc, Grade C means more serious lithium deposition: most of the arc has gray-black or silver lithium deposition materials and the lithium deposition process is strip-shaped, Grade D means serious lithium deposition: not only is there obvious lithium deposition at the arc, but also lithium deposition occurs around the arc, showing a state of lithium deposition spreading from the arc to the surrounding.

[0096] The results of the various embodiments and comparative examples obtained by the above detection method are shown in Tables 4 to 6 below.

[0097] Table 4

[0098]

[0099]

[0100] Table 5

[0101]

[0102] Table 6

[0103]

[0104]

[0105] It can be seen from the data in Table 4 that, while ensuring that the battery energy density is at the same level, by comparing Examples 1-14 with Comparative Examples 1-8, it can be seen that by controlling the content of the boron-containing compound in the additive included in the electrolyte and the diameter of the through-hole structure provided in the arc region on the negative electrode sheet, and controlling 20≤D / A1≤120, the arc lithium precipitation problem of the wound lithium-ion battery can be effectively improved, and the cycle life of the lithium-ion battery can be effectively extended.

[0106] It can be seen from Tables 5 and 6 that no matter whether the composition of the electrolyte is changed, or the parameter conditions of the through-hole structure in the negative electrode sheet are changed, or the positive electrode treatment method is used to control the positive and negative electrode capacity ratio, the effects achieved are better than those of Comparative Examples 1-8 in Table 1, which is sufficient to prove that the present invention has the effect of improving arc lithium deposition of wound lithium-ion batteries and extending the cycle life of lithium-ion batteries by providing a through-hole structure in the arc region of the negative electrode sheet and controlling the ratio (D / A1) of the content of the boron-containing compound in the additive included in the electrolyte to the diameter of the arc region on the negative electrode sheet where the through-hole structure is provided within the parameter condition range of the present invention.

[0107] By comparing Examples 1-7 with Examples 8-14 in Table 4, it can be seen that by controlling the ratio of S1 / S2, the boron-containing compound, the sulfur-containing heterocyclic compound A2, other additives A3, and the ratio of A2 / A1 within the scope of the present invention, the arc lithium deposition of the wound lithium ion battery can be further improved and the cycle life of the lithium ion battery can be extended.

[0108] By comparing the results of Examples 26-33 in Table 6 with the results of Examples 34-41, it can be seen that controlling the spacing and distribution width of the through-hole structure, the porosity and silicon content of the negative electrode sheet within the scope of the present invention can further improve the arc lithium deposition of the wound lithium-ion battery and extend the cycle life of the lithium-ion battery.

[0109] By comparing the results of Examples 42-43 in Table 6 with the results of Examples 44-45, it can be seen that the distribution particle size of the powder in the negative electrode active material layer is within the scope of the present invention, which can further improve the arc lithium deposition of the wound lithium ion battery and extend the cycle life of the lithium ion battery.

[0110] By comparing the results of Examples 1-2 with the results of Example 46, it can be seen that by thinning or punching the arc area of ​​the positive electrode sheet so that the ratio of the negative electrode capacity to the positive electrode capacity reaches within the range of the present invention, the arc lithium deposition of the wound lithium-ion battery can be further improved and the cycle life of the lithium-ion battery can be extended.

[0111] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A wound lithium-ion battery, comprising an electrolyte, a negative electrode sheet, and a positive electrode sheet; characterized in that: The electrolyte includes an organic solvent and a first additive; the first additive includes a boron-containing compound, and the mass proportion of the boron-containing compound in the electrolyte is A1%; The negative electrode sheet includes a plurality of first straight regions and a plurality of first arc regions, and the positive electrode sheet includes a plurality of second arc regions corresponding to the first arc regions; The first arc region is provided with a through hole structure, and the aperture of the through hole structure is D μm; Among them, A1 and D satisfy: 20≤D / A1≤120.

2. The wound lithium-ion battery according to claim 1, characterized in that: 0.3≤A1≤2; and / or, 20≤D≤200, preferably 50≤D≤150; And / or, the boron-containing compound is selected from one or more of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium dicyanooxalatoborate, lithium bismalonate borate, lithium (2-fluoromalonate)difluoroborate, lithium bis(salicylate)borate, lithium methanedisulfonate difluoroborate, lithium bis(difluorophosphoryloxy)difluoroborate, and lithium bis(1,1,1,4,4,4-hexafluorobutyl-2,3-diol)borate.

3. The wound lithium ion battery according to claim 1 or 2, characterized in that: The additive further includes a second additive; the second additive includes a sulfur-containing heterocyclic compound; Preferably, the wound lithium-ion battery further comprises a third additive, and the third additive comprises at least one of succinonitrile, adiponitrile, glutaronitrile, hexanetrinitrile, ethylene glycol bis(propionitrile) ether, glycerol trinitrile, and 2,4,6-tricyano-1,3,5-triazine.

4. The wound lithium ion battery according to claim 3, characterized in that: The mass proportion of the sulfur-containing heterocyclic compound in the electrolyte is A2%, 1≤A2≤4; preferably, 1.5≤A2 / A1≤5; And / or, the sulfur-containing heterocyclic compound includes at least one of the following structural formulas:

5. The wound lithium ion battery according to claim 1 or 2, characterized in that: The organic solvent comprises a first solvent and a second solvent, wherein the first solvent is selected from carboxylic acid ester compounds containing 4 to 6 carbon atoms, and the second solvent is selected from at least one of ethylene carbonate and fluoroethylene carbonate.

6. The wound lithium ion battery according to claim 5, characterized in that: The first solvent is selected from one or more of ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, methyl isobutyrate, ethyl isobutyrate and various fluorinated compounds of these compounds.

7. The wound lithium ion battery according to claim 5, characterized in that: The amount of the first solvent added to the electrolyte is S1 wt%, 30≤S1≤70; and / or the amount of the second solvent added to the electrolyte is S2 wt%, 15≤S2≤40; Preferably, 1.5≤S1 / S2≤3.

8. The wound lithium ion battery according to claim 1 or 2, characterized in that: In the first arc region, the spacing between adjacent through-hole structures is 100-800 μm, preferably 200-600 μm; And / or, the distribution width of the through hole structure in the first arc region is 2-10 mm.

9. The wound lithium ion battery according to claim 1 or 2, characterized in that: The porosity of the negative electrode sheet is 10%-40%.

10. The wound lithium ion battery according to claim 1 or 2, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, and the silicon content in the negative electrode active material layer is 2%-30%; And / or, the distribution particle size of the powder in the negative electrode active material layer satisfies Dv10: 3-8 μm, Dv50: 8-15 μm, Dv90: 15-25 μm.

11. The wound lithium ion battery according to claim 1 or 2, characterized in that: The second arc region is provided with a concave hole structure; And / or, the thickness of the positive electrode active material layer in the second arc region is smaller than the thickness of the positive electrode active material layer in the adjacent positive electrode sheet region.